Sensitivity and Specificity of the UCSD Performance-based Skills Assessment (UPSA-B) for Identifying Functional Milestones in Schizophrenia - Mausbach, Brent T (2011)
Schizophrenia is a highly debilitating illness that often results in disruption to independent living and employment. However, “gold standard” methods of assessing functional abilities to achieve these milestones are still lacking. In a sample of 367 individuals with schizophrenia, we examined the sensitivity and specificity of the Brief UCSD Performance-based Skills Assessment (UPSA-B) to predict both residential and employment status. Of all individuals residing independently, 75.9% scored 78 or above on the UPSA-B, and of all individuals not residing independently, 59% scored below 78 on the UPSA-B. Of individuals who were employed, 73.9% scored above 82 on the UPSA-B, and of those not employed, 57.8% scored below 82. These results expand upon both the population base and functional milestones with which the UPSA-B is validated, although future work should examine whether the UPSA-B can be used as a decision aid in the likelihood of success in a longitudinal study, such as at critical transitions (post-hospitalization, cessation of supported housing).